Wind chill for cattle - Ames, D.R. (Kansas State University. Agricultural Experiment Station, 2011)
Cattle hides were exposed to cold-wind combinations ranging from -10 ̊F to 35 ̊F and 0 to 35 mph. Heat flow through hides (including hair) was measured and plotted as a function of wind velocity. Prediction equations for heat flow at different cold-wind combinations were formulated and compared with the human wind-chill index used by the U.S. Weather Bureau. Results indicate that wind-chill effects for humans and cattle are similar at low wind velocities (less than 25 mph) but differ at wind velocities greater than 25 mph. over the range of wind velocities studied, a cubic relationship was found for cattle hides rather than the quadratic relationship of the human wind-chill index.
Keywords: Beef; Wind chill; Wind velocity